Genome Microscale Heterogeneity among Wild Potatoes Revealed by Diversity Arrays Technology Marker Sequences - Alessandra Traini; Massimo Iorizzo; Harpartap Mann; James M. Bradeen; Domenico Carputo; Luigi Frusciante; Maria Luisa Chiusano (International Journal of Genomics)
Tuber-bearing potato species possess several genes that can be exploited to improve the genetic background of the cultivated potato Solanum tuberosum. Among them, S. bulbocastanum and S. commersonii are well known for their strong resistance to environmental stresses. However, scant information is available for these species in terms of genome organization, gene function, and regulatory networks. Consequently, genomic tools to assist breeding are meager, and efficient exploitation of these species has been limited so far. In this paper, we employed the reference genome sequences from cultivated potato and tomato and a collection of sequences of 1,423 potato Diversity Arrays Technology (DArT) markers that show polymorphic representation across the genomes of S. bulbocastanum and/or S. commersonii genotypes. Our results highlighted microscale genome sequence heterogeneity that may play a significant role in functional and structural divergence between related species. Our analytical approach provides knowledge of genome structural and sequence variability that could not be detected by transcriptome and proteome approaches.